Omic molecular characterization of a Bacillus amyloliquefaciens strain isolated from the paiche Arapaima gigas microbiota with antagonistic activity against fish pathogenic bacteria - Feria Zevallos, Manuel Alberto (2019)
The characteristics of a strain of Bacillus amyloliquefaciens isolated from the intestine of Arapaima gigas, selected for its ability to generate inhibition of multiple pathogenic bacteria of fishes were analyzed by using molecular tools such as PCR and mass spectrometry - MALDI TOF / TOFM. The results showed through PCR that this strain has key genes for the generation of antimicrobial peptides such as bmyB (bacillomycin L synthetase B), fenD (fengycin synthetase), srfAA (subunit 1 surfactin synthetase), bacA (bacilysin biosynthesis protein) and iturin (iturin A). In addition, by mass spectrometry analysis were detected bacteriocins (plipastatin, gramicidin, fengycin, surfactin), intestine binding proteins (like-enolase), antimicrobial peptide transport proteins (ABC-transporters) and immune system stimulation proteins like flagelin. Collagenase, chitinases and xylose-isomerases proteins were also detected that contribute to the digestion and assimilation process. All these results allow to consider the multiple benefits of this strain to be used as a probiotic in fish culture.